Path generation with dwells in the optimum dimensional synthesis of Stephenson III six-bar mechanisms. (February 2020) - Peón-Escalante, R.; Jiménez, F. Cuenca; Escalante Soberanis, M.A.; Peñuñuri, F.
Highlights: The spherical Stephenson III mechanism with dwells is synthesized for the first time. The obtained equations for the kinematic analysis are clear and concise. An accurate way for computing velocity and acceleration is presented. Higher order synthesis equations are automatically computed from a position equation. Abstract: The optimal dimensional synthesis for Stephenson III six-bar linkages, planar and spherical, is presented. The requirement for dwells of the output link and the path generation task are also addressed. We propose a formulation for the synthesis in which the velocity of the output link is calculated by using dual functions. The condition for dwell is obtained through the minimization of the angular velocity, using the evolutionary algorithm known as Differential Evolution. We perform a numerical comparison between the use of the dual numbers and finite differences for computing the velocity and acceleration coefficients of the output link for the spherical case. The results exhibit the importance of having a precise method for computing derivatives.